Autoimmune diseases after hepatitis B immunization in adults: Literature review and meta-analysis, with reference to 'autoimmune/autoinflammatory syndrome induced by adjuvants' (ASIA). Issue 38 (11th September 2018) - Elwood, J. Mark; Ameratunga, Rohan
Abstract: Background: To assess if hepatitis B vaccination in adults is causally associated with autoimmune diseases. Such causation has been claimed based mainly on case reports and uncontrolled studies, and a syndrome 'Autoimmune/autoinflammatory Disorder Induced by Adjuvants' (ASIA) has been claimed to be linked to immunization, particularly hepatitis B vaccination. Methods: Review of peer-reviewed literature from January 1990 to March 2017 identifying controlled studies with documented incidence of autoimmune diseases occurring after hepatitis B vaccinations in adults. From 1297 studies identified, 259 were further assessed and 49 reviewed further; 19 relevant papers reporting 21 results are reviewed here, and 14 results included in a meta-analysis. Results: Overall no association between hepatitis B vaccination and the onset of autoimmune diseases was seen. The overall odds ratio was 1.06, with 95% confidence limits of 0.93–1.21, with non-significant heterogeneity. Only one study showed a significant excess risk between hepatitis B immunisation and autoimmune disease. Conclusions: Despite multiple case reports, there is no reliable scientific evidence of autoimmune diseases being caused by hepatitis B vaccinations.